Molecular Characteristics of Chitosan and Structure of its Films Formed from Water Solutions of Acetic and Hydrochloric Acids - Belnikevich, Nina; Rosova, Elena; Malakhova, Irina; Krasikov, Valery; Zoolshoev, Zoolsho; Elena Popova, Elena Popova; Saprykina, Natalia; Elyashevich, Galina Galina (Journal of Research Updates in Polymer Science, 2016)
Molecular characteristics of chitosan in diluted water solutions of acetic and hydrochloric acids were studied by viscometry, dynamic light scattering, and thin layer chromatography. Chitosan molecules were found to undergo destruction in the solutions of hydrochloric acid and its mixtures with acetic acid. The structure of the chitosan films cast from these solvents was studied by DSC, TGA, and SEM. As shown by electron microscopic data, all the films had an amorphous-crystalline structure but the films prepared from chitosan solutions in diluted hydrochloric acid were characterized by a higher degree of crystallinity. It was supposed that a lower molecular mass of chitosan molecules in the hydrochloric acid solutions results in more extended conformations providing a higher capability of self-organization and formation of regular supermolecular structure. The difference in crystal modification in structure of the films cast of these acids was observed. It was found that the films prepared from the mixtures of acids had a spherulite structure and the crystal modification like ones cast from hydrochloric acid, but with a lower degree of crystallinity.